A "turn-on" fluorescent probe for the detection of Cu2+ in living cells based on a signaling mechanism of NN isomerization. (17th May 2016) - Cao, Shuo; Jin, Qiaoying; Geng, Lin; Mu, Lingyun; Dong, Shouliang
Abstract : A "turn-on" probeA based on coumarin with a mechanism of NN isomerization was developed for detecting Cu 2+ in living cells. Abstract : A novel fluorescent probeA based on coumarin associated with a NN double bond was conveniently designed and synthesized for Cu 2+, and both rapid colorimetric and fluorescence turn-on detection can be achieved, showing a visible color change from pink to yellow and a significant fluorescence enhancement, respectively. The probe exhibits high selectivity toward Cu 2+ over other metal ions and excellent sensitivity with a detection limit of 20 nM, and it can be monitored in a wide range of pH (3–10) in aqueous systems. Besides, the probe has been applied in living cells.